Studi Tipologi Strategi Supply Chain dan Kinerja pada Perusahaan Manufaktur di Jawa Timur - Handriyono -; Djumilah Zain; MS Idrus; Armanu Thoyib (Jurnal Aplikasi Manajemen, 2012)
In line with the Increasingly tight competition along with the higher and more varied customers’ demand, companies do not stock pile their invnory in warehouses anymore, but they are required to be subtle in integrating the flow of information and goods from suppliers , manufacturers, distributors, outlets, and up to the costumers, which is known as Supply Chain Management (SCM).. Currently, SCM has become the primary concern of every company to improve its operating performance. The changing paradigm of compettion, which was initially amongst companies, now has moved to be amongst chains. In addition, as the information technology is getting more advanced. SCM should be applied in order not only to maintain its existence but also to become strategic assets leading to improvement of the company’s operating performance. This study is aimed at investigating the integration strategy of suppliers and customers using a sample of 24 (twenty four) cosmetic companies in East Java Province. After the identification of sample and conducting a factor analysis, it is found that there are five different strategies in which each of them is characterized by different arc of integration which represents the directions of suppliers or customers.. The findings show that the five integration typology areas, which are inward facing, inward facing skewed to customers, inward facing skewed to supplier, periphery facing, and outward facing, have significant differences among those five SCM integation typologies, particularly in the financial perspective criteria. Meanwhile, no significant differences are shown seen from the other two perspectives, namely customer perspective and internal business process perspective.Keywords: Supply Chain Management, Arc of integration